Pengembangan Media Edukasi Iteraktif Tentang Adab Dalam Islam Menggunakan Metode Multimedia Development Life Cycle (MDLC): Pendahuluan, metode, hasil, kesimpulan - Ali Ikhwan; Tutur Arbaim Sitakar; Satria Pratama; Iqbal FirzaTullah (GLOBAL SCIENTS PUBLISHER, 2026)
Learning media plays an important role in increasing students' interest and understanding of the material presented. This study aims to develop a multimedia-based interactive learning media application for 1st grade elementary school students on Theme 5: Experience, Subtheme 1: Childhood Experience. The development method used is the Multimedia Development Life Cycle (MDLC) which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. The application was developed using Adobe Flash CS6 Professional by utilizing various multimedia elements such as text, images, animation, audio, video, quizzes, and educational games. The integration of these elements aims to create a more interesting, interactive, and enjoyable learning process for students. Application testing was conducted to assess the feasibility and effectiveness of the developed learning media. The results showed that the application obtained a rating percentage of 92.92% with the category of